The adaptability of Industrial Revolution 4.0 technology in valuation field / Asmida Shafina Osman - Osman, Asmida Shafina (2023)
The research study investigates the adaptability and effects of Industrial Revolution 4.0 (IR4.0) technologies in the property valuation field in Malaysia. By integrating advanced technologies like big data analytics, artificial intelligence (Al), machine learning (ML), geographic information system (GIS), and drones, valuers have witnessed significant improvements in efficiency, accuracy, and cost savings. The study reveals that the majority of valuers have embraced IR4.0 technologies, finding them beneficial for simplifying work processes and making informed decisions. Drones and GIS systems have been utilized for property inspections and site analysis, while Al and ML algorithms have automated data analysis, leading to improved decision-making. The integration of digital platforms and applications has further enhanced connectivity and collaboration among valuers. The study emphasizes the importance of staying updated with the latest technological advancements to remain competitive and deliver reliable services. The support of professional organizations, such as the Royal Institution of Surveyors Malaysia (RISM), will be crucial in guiding valuers through the challenges and opportunities presented by IR4.0 in the valuation field. By embracing these technologies, valuers can revolutionize the industry, ensuring a progressive and successful future for property valuation in Malaysia.